PEREMPUAN DALAM PERSPEKTIF HAM DAN ISLAM - sabhamis sabhamis (Jurnal Ulunnuha, 2017)
The goal of the is basically to protect all human beings.  However, its realization is disturbed by various interests.  This is so because of the difference philosophical life each states embraces. Dealing with multi interpretation about woman as individual creature, how does the Qur’an regard the woman in the perspective of human rights?  This paper tries to reconstruct the common and bias interpretation so that human being gradually put the woman in portion.